Green Spaces in the Urban Environment: A case study of Varanasi City - Goswami, Kaushalendra Prakash; Kumari, Niraj (National Geographical Journal of India, 2022)
The green belts in urban area are considered to be an integral part of the urban landscape lending beauty to the concrete of which the city is made. It gives fresh environment and release of mental stress caused by the hectic life. Varanasi city is the centre of Indian tradition religion, culture practices and rituals, rich in heritage and colours of India. So as to be described as mini India representing all the colours of Indian diversity, a city having a sense of its own, breathing and living in daily homage paid to the god and goddesses. The city as old as the culture of the country itself, built centuries ago is now wanting more space to breath and grow to come out of the old maze like narrow streets which has become its identity, with crumbling buildings which still hold the mark of its beauty, buried under dust of lack of maintenance it is asking for attention. Varanasi is a city in mess, with uneven development, and unplanned expansion of unapproved colonies. The city which is very significant as a religious and tourist centre, at present is in need of urban forestry which is only about less than 5 % and which actually should be 20% for urban areas. The question that arises is that in spite of its significant as one of the important cities in the north why have the care or initiative not been taken by the State or central government. The paper highlights the work done by the forest division to create green belts and plant them by social forestry schemes to make the city ecologically balanced.